2012
DOI: 10.1177/0963662512463510
|View full text |Cite
|
Sign up to set email alerts
|

Microblogging and nanotweets: Nanotechnology on Twitter

Abstract: The social web represents a new arena for local, national and global conversations and will play an increasing role in the public understanding of science. This paper presents an analysis of the representations of nanotechnology on Twitter, analysing over 24,000 tweets in terms of web metrics, latent semantic and sentiment analysis. Results indicate that most active users on nanotechnology are distributed according to a power law distribution and that web metric indicators suggest little conversation on the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
12

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 49 publications
2
46
0
12
Order By: Relevance
“…In a network based on co-occurrence, high centrality means a high degree of salience and visibility of a semantic concept or entity in conversations (Doerfel & Connaughton, 2009). Various prior studies have used this approach to identify import themes in public discussions online (Oh, Kwon, & Rao, 2010;Veltri, 2012). Accordingly, in a network based on co-occurrence of country names, countries with a high degree of centrality are considered highly salient and visible.…”
Section: Applying Network Analysis To International Relationsmentioning
confidence: 99%
“…In a network based on co-occurrence, high centrality means a high degree of salience and visibility of a semantic concept or entity in conversations (Doerfel & Connaughton, 2009). Various prior studies have used this approach to identify import themes in public discussions online (Oh, Kwon, & Rao, 2010;Veltri, 2012). Accordingly, in a network based on co-occurrence of country names, countries with a high degree of centrality are considered highly salient and visible.…”
Section: Applying Network Analysis To International Relationsmentioning
confidence: 99%
“…De hecho, varias investigaciones han afirmado que Twitter es un espacio para compartir información, para hablar, pero no para escuchar, un entorno donde se desarrolla un proceso de comunicación unidireccional y no bilateral (Lovejoy, Waters y Saxton, 2012;Waters y Jamal, 2011), registrando escasas conversaciones (Veltri, 2014).…”
Section: Proceso De Comunicaciónunclassified
“…visualization of clusters of similar tweets [14,15], recommendation of hashtags [16], sentiment analysis [17,18], detection of events or common topics [19,20], clustering of tweets [21,22], etc.). However, in most cases it can be observed that the treatment of the tweet components (mainly the words contained in the body of the tweet and its hashtags) is purely syntactic.…”
Section: Related Workmentioning
confidence: 99%
“…Mathiesen et al [24] build graphs of terms, where the edges are weighted by their co-occurrence, and study the communities present in these graphs. Veltri [21] also uses the co-occurrence between words to classify tweets related to the Nanotechnology domain. The lack of a semantic treatment of the content of the tweets is the main shortcoming of all these approaches.…”
Section: Related Workmentioning
confidence: 99%